KEUNTUNGAN DAN KERUGIAN PENJAMINAN MUTU BERDASARKAN UJI MEMASTIKAN KECERMATAN (POCT) - Hartono Kahar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
Laboratory examination especially for critical care such as emergency care, intensive care has been developed near the site of patientcare which is referred to point-of-care testing (POCT). As to the definition of POCT, there are many synonyms such as ancillary testing,satellite testing, and bedside testing, near patient testing, home testing, self-management, patient self-management, remote testing andphysician’s office laboratories. Based on evidence-based POCT, the National Academy of Clinical Biochemistry (NACB) has recommendedsome POCT such as coagulation tests, transcutan bilirubin testing, marker for acute coronary syndromes, diabetes mellitus, drugsand ethanol, Infectious disease testing, occult blood test, pH testing, renal function test, intraoperative PTH, renal function test andreproduction test. Some researchers conclude that performing POCT for critical care is efficient, while others found it not efficient,therefore, careful assessment of the advantages and disadvantages is important when implementing POCT. Nurses are the personnelin the acute care unit who often perform POCT; however they desire that laboratory personnel take the responsibility, therefore it isimportant to discuss which personnel are appropriate to conduct quality control of POCT.